CONTEMPORARY MIGRANT CRISIS WITH THE SPECIAL OVERVIEW OF THE PROTECTION OF CONSTITUTIONAL RIGHTS OF THE CITIZENS OF IMMIGRATION COUNTRIES (Heritage, 2024)
The contemporary migrant (refugee) crisis that began in 2010 in the countries of North Africa and the Middle East is by no means accidental, but a very well-planned and executed migration of people. This plan slowly leads to the formation of a completely new world order in such a way as to destroy the previous national one, and create a completely new limited sovereignty. The de-sovereignation of nation-states has become a scourge of the modern age. A typical example is the European Union, which, in the era of the contemporary migrant crisis, has set itself a great challenge and task, to preserve the national identity of its member states. In the paper, the authors presented the legal and institutional framework for the protection of basic human rights of migrants. The paper contains a special reference to respect for the constitutional rights of citizens of the countries of immigration in the age of the migrant crisis. The contemporary migrant crisis has led to an enormous increase in people smuggling, but also influenced the increase in human trafficking. In the paper, the authors point to the distinction between human smuggling as a criminal offense against public order and peace and human trafficking as a criminal offense against humanity and other goods protected by international law. In the final deliberations, it was pointed out the necessity of respecting international documents, encouraging national, regional and global cooperation, as well as public condemnation of discrimination and hate speech.
Keywords: migrant crisis, de-sovereignization, relocation of people, migrant smuggling, protection of human rights